ANALISIS USAHA DAN PEMASARAN JAMUR TIRAM PUTIH (Pleurotus Ostreatus) STUDI KASUS DI KELURAHAN TANGKERANG TIMUR KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Arif Rahman Zikri; Shorea Khaswarina; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: 1) identifying the white oyster mushroom cultivation techniques which are run by farmers King Spora Farm. 2) analyzing the costs and revenue of white oyster mushroom cultivation is carried out by farmers King Spora Farm. 3) analyzing the cost, margin and marketing efficiency of white oyster mushroom business by farmers King Spora Farm. The research was do from January 2015 to April 2015. The method used is the case study method. Results showed white oyster mushroom cultivation techniques the farmers get optimal results after doing research on the experience during to farm. White oyster mushroom farming requires production cost of Rp 16,651,822,- each production cycle. Net income derived from the cultivation of white oyster mushroom Rp 6,298,178,- each production cycle and gross revenue of Rp 22.950.000,- each production cycle. Results of the analysis of white oyster mushroom farming obtained RCR of 1,38. BEP white oyster mushroom farming Rp 13,206,407,- each production cycle or 433,17 kg of white oyster mushroom each production cycle. Thus, white oyster mushroom farming viable and profitable. Marketing white oyster mushroom of King Spora Farm there are two marketing channels, namely channel I (farmer to consumers) and channel 2 (farmer to traders to consumers). Channel I marketing efficiency by 0.62%, while marketing channel II by 1.75%, so that the white oyster mushroom cultivation is more efficient on channel I.   Keywords: cultivation, farming, marketing, white oyster mushrooms.